EL PLAGIO Y SU RELACIÓN CON LOS PROCESOS DE ESCRITURA ACADÉMICA - Ochoa S., Ligia; Cueva Lobelle, Alberto (Forma y Función, 2014)
Plagiarism has become a great concern within the academic community. Among the diverse factors explaining the phenomenon, one of the most relevant ones is related to academic writing processes. The article presents the results of a research project regarding this factor, obtained from interviews with professors and students of the School of Human Sciences of the Universidad Nacional de Colombia. According to the professors, the cause of the problem of plagiarism in writing is the deficient education and habits students acquire in school, where they are not taught to cite properly. The students believe they resort to plagiarism because they have writing problems and they have not been adequately prepared to produce academic texts.